The battle for 'Middle-earth': The constitution of interests and identities in The Hobbit dispute. (November 2017) - McLaughlin, Colm; Bridgman, Todd
This article draws on an industrial dispute over the filming of The Hobbit in New Zealand in 2010 to contribute to the theorisation of the interplay between interests and identities and our understanding of mobilisation and collective identity. While industrial disputes are typically viewed as conflict between groups with opposing material interests, this may miss the way in which both the identities of those involved and their interests are discursively constituted in articulatory processes. Specifically, we apply Laclau and Mouffe's discourse theory and in doing so demonstrate that the dispute was more than a conflict over working conditions, it was a hegemonic struggle to fix meaning. In making this conceptual contribution we highlight a tendency within industrial relations analysis to reify interests.